AL-MAQAMAH AL-‘ARABIYAH WA ZHAHIRAH TADAKHUL AL-AJNAS AL-ADABIYAH - Arif Karkhi Abukhudairi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
The article aimed to study the phenomenon of overlapping literary genres in the Arabic literary works by identifying the types of literary genres and providing examples of the premises of Budaiya and Hariri, to draw the distinction made by this artistic phenomenon, and to make the most of it. The research ended with several results. The most important one was that Badi'uz-Zaman al-Hamdani succeeded in inventing a new art in Arabic literature, the art of establishing. This achievement was undoubtedly great and recorded by the scholars. However, the completion of Budaiya did not stop at this limit. It had also succeeded in creating an artistic phenomenon which did not pay attention to the past scholars’ views — i.e., the phenomenon of overlapping literary genres. Moreover, his student, Hariri, developed it. The authors were able to employ it to achieve their artistic, linguistic and social goals.